The role of task-supported language teaching in EFL learner’s writing performance and grammar gains - Sadeghi, Karim; Fazelijou, Esmaeil (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Recent research in SLA advocates the use of task as a useful class activity claiming that task approximates language use in the context of classroom to the way language is used in the real world. Framed under a cognitive framework to task-based language teaching, this study was set out to investigate whether task-based oriented activities bear any superiority to that of more traditional ones evident in PPP (Presentation-Practice-Production) model. Twenty eight female pre-intermediate participants studying English in one language school in Urmia, Iran, took part in the study. They participated in ten half-an-hour long sessions of instruction during which they were instructed four structural points: simple past, simple present, present continuous, and ‘There is/There are/How much/How many’ structures. PPP group received their treatment through conventional approach and task-based group, through task-oriented activities. The quantitative analysis performed on the post-test (consisting of a grammar recognition test and a writing activity) suggested that participants in the PPP group did significantly better in the grammar recognition section of the post-test. However, their counterparts in the task group gained better scores in the writing section of the test. Further findings and implications are discussed in the paper.